Chemical Composition and Evaluation of the α-Glucosidase Inhibitory and Cytotoxic Properties of Marine Algae Ulva intestinalis, Halimeda macroloba, and Sargassum ilicifolium. (23rd November 2020) - Nazarudin, Muhammad Farhan; Isha, Azizul; Mastuki, Siti Nurulhuda; Ain, Nooraini Mohd.; Mohd Ikhsan, Natrah Fatin; Abidin, Atifa Zainal; Aliyu-Paiko, Mohammed
Abstract : Seaweed has tremendous potentials as an alternative source of high-quality food products that have attracted research in recent times, due to their abundance and diversity. In the present study, three selected seaweed species commonly found in the Malaysian Peninsular, Ulva intestinalis, Halimeda macroloba, and Sargassum ilicifolium, were subjected to preliminary chemical screening and evaluated for α -glucosidase inhibitory and cytotoxic activities against five cancer cell lines. Chemical composition of U. intestinalis, H. macroloba, and S. ilicifolium methanolic extracts was evaluated by Gas Chromatography-Mass Spectrometry (GC-MS) analysis. Our results revealed the highest total carotenoids (162.00  μ g g −1 DW), chlorophyll a (313.09 ± 2.53  μ g g −1 DW), and chlorophyll b (292.52 ± 8.84  μ g g −1 DW) concentrations in U. intestinalis . In the α -glucosidase inhibitory activity, S. ilicifolium demonstrated the lowest efficacy with an IC50 value of 38.491 ppm compared to other species of seaweed. H. macroloba extract, on the other hand, was found to be the most cytotoxic toward MCF-7 and HT 29 cells with IC50 of 37.25 ± 0.58 and 21.32 ± 0.25  μ g/mL, respectively, compared to other cell lines evaluated. Furthermore, H. macroloba extract was also found to be less toxic to normal cell (3T3) with IC50 of 48.80 ± 0.11  μ g/mL. U. intestinalis extract exhibited the highest cytotoxicity toward Hep G2 cells with IC50 of 23.21 ± 0.11  μ g/mL, whereas S. ilicifolium was less toxic to MDA- MB231 cell with IC50 of 25.23 ± 0.11  μ g/mL. Subsequently, the GC-MS analysis of the methanolic extracts of these seaweed samples led to the identification of 27 metabolites in U. intestinalis, 22 metabolites in H. macroloba, and 24 metabolites in S. ilicifolium . Taken together, the results of this present study indicated that all the seaweed species evaluated are good seaweed candidates that exhibit potential for cultivation as functional food sources for human consumption and need to be promoted.